High-Yield Biosynthesis Process and Characterization of Brolucizumab - Hu, Xiaoyue; Huang, Shuaiyi; Luo, Tao; Wang, Yapeng; Lu, Jianguang; Feng, Jun (Pharmaceutical Fronts, 2025)
Brolucizumab was the first single-chain fragment variable (scFv) antibody approved by the FDA for the treatment of age-related macular degeneration (AMD). However, the manufacturing process of brolucizumab remains rarely reported. This study aimed to explore a bioprocess for the production of brolucizumab, where it is expressed as inclusion bodies (IBs) in Escherichia coli (E. coli) BL21 (DE3) cells. In this work, IBs were initially obtained via high cell density fermentation (HCDF) at a high expression level of 30 g/L, followed by denaturation, refolding, and purification to obtain brolucizumab. The refolding parameters were systematically optimized to ensure a high yield of brolucizumab, with 413 mg of the target protein from a 1-L fermentation broth, and purity exceeding 98%. In addition, the amino acid sequence coverage and disulfide bond pairing of the protein were further verified. The results confirmed that brolucizumab has excellent structural integrity, high purity, and notable biological activity. The biosynthetic process holds significant potential for therapeutic applications of brolucizumab and provides valuable insights for the further development of additional scFv bioprocesses.
Keywords: age-related macular degeneration; brolucizumab; inclusion bodies refolding; recombinant expression